Multicultural Education From the Position of a Dialogue Approach - Karine Y. Breshkovskaya; Nina S. Ezhkova (Publishing house "Sreda", 2020)
The article presents a scientific analysis of the problem of multicultural education. The dialogue approach as a methodological component of modern multicultural education, based on the position of the dialogue of cultures and cultural pluralism is characterized in the article. The concept of "dialogue" is characterized as the basis for interaction, support for the subjective position of the individual, its spiritual development in the educational process, and a way to unite different cultures. Cultural identity is highlighted as a favorable factor for introducing children to the world of culture and assimilating the values of other cultures; the relationship between cultural identity and cultural diversity is revealed, as well as the possibility of using such unity in building technologies of modern multicultural education. The methodological aspects of multicultural education of preschoolers: the process of developing values in preschoolers is creation of a multicultural educational environment. The author identifies the levels of development of value concepts in preschoolers: cognitive, evaluative, and activity. The author gives a meaningful description of pedagogical work with children at each selected level, describes the leading positions that should be used in the development of children's ideas about people of other nationalities. Methods. During the study, the authors carried out a theoretical analysis of the literature on the problem. It is concluded that in the process of implementing the principle of dialogics in multicultural education, children are prepared to understand another culture, to recognize the surrounding diversity.